51 Working Collaboratively: Geriatrician Input in Older Patients Undergoing Emergency Laparotomy Reduces Overall Length of Stay - A Complete Audit Loop. (6th February 2020) - Khan, K A; Richters, M; Mubarak, A; Thorn, C; Chalstrey, S; Gunasekera, S
Abstract: Background: Great Western Hospital is a busy district general hospital with a catchment population of 340, 000. Target population of this study was elderly patients aged >70 undergoing Emergency Laparotomy (EL). Introduction: Approximately 8% of the population is aged over 75 years and operations in this patient group account for 23% of all surgical procedures. The 2010 National Confidential Enquiry into Patient Outcome and Death report "An Age Old Problem", suggested routine daily input from Geriatrics should be available to elderly patients undergoing surgery. This study focuses at the impact of Geriatrician input for EL patients with primary outcome of reduction in Length of Stay (LoS). Methods: The service was designed with allocation of 4 hours per week of Consultant Geriatrician and 2.5 days per week of a Clinical Innovation Fellow (CIF) time. The existing team of surgical junior doctors, nursing and allied health professionals carried out plans suggested by the geriatrician. Retrospective data (Prior to service initiation) for the emergency laparotomy patients >70 years, was collected from December 2015-May 2016. Prospective data collected from February 2018 – July 2018 for EL patients aged > 70, patients with inpatient stay > 7 days, patients with delirium/ inpatient falls. Length of stay and Inpatient mortality were compared between the two cohorts. Intervention: Prior to the establishment of this service the medical support was provided on ad-hoc basis. Funding was obtained from local postgraduate medical education for CIF and twice weekly consultant led ward rounds were carried out. Patients were recruited from hospital database and from a referrals book kept at surgical ward. Results: 45 patients were included in prospective study and Mean LoS was 17.8 days, which was reduced from 22.5 days prior to Geriatrician involvement (N=56). Average 4.7 days per patient were saved. IP mortality was 8.8% (2/4 deaths were palliative resections) after geriatrician input compared to 8.9% previously. 6.6% of patients had a new medical diagnosis, 24.4% patients were followed up in prospective cohort. Conclusions: This study suggests the regular geriatrician input reduces the inpatient LoS. A day stay at surgical ward costs roughly £250, for 45 patients in last six months it saved approximately £52, 875.